Wykorzystanie koncepcji opcji realnych do pomiaru wartości projektów inwestycyjnych - Rudny, Włodzimierz (The article analyses the recent concept of real options as applied to valuation of investment projects. Real options are defined and the basic typology of them is presented. Valuation of real options using binominal trees is analysed in detail. Examples of valuation and application of selected options conclude the paper., 2005)
The article analyses the recent concept of real options as applied to valuation of investment projects. Real options are defined and the basic typology of them is presented. Valuation of real options using binominal trees is analysed in detail. Examples of valuation and application of selected options conclude the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 326-348